PAI Teacher's Strategy in Implementing KMA No. 347 of 2022 at MAN 2 Langkat Tanjung Pura - Muamar Al Qadri; Sufriansyah; Muhammad Rizaldi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to describe the strategies of Islamic Religious Education (PAI) teachers in implementing Minister of Religious Affairs Decree (KMA) No. 347 of 2022 at MAN 2 Langkat Tanjung Pura. This regulation served as the foundation for the implementation of the Merdeka Curriculum in piloting madrasahs, emphasizing learning outcomes, teacher autonomy in formulating learning objectives, and the use of more varied assessments. Although KMA No. 347 has now been replaced by KMA No. 450 of 2024, its implementation still provides valuable experiences for PAI learning practices in madrasahs. This research employed a qualitative approach with structured interviews conducted with the principal, vice principal of curriculum affairs, and PAI teachers. The collected data were analyzed thematically to identify patterns of implementation strategies, learning innovations, and challenges encountered. The findings reveal that the school supported teachers through policies, training, and supervision in implementing the regulation. At the curriculum level, teaching instruments such as teaching modules, annual programs, and semester programs were developed in accordance with the regulation and tailored to the needs of PAI subjects. Teachers applied collaborative learning, problem-based learning, and project-based learning strategies to foster students’ critical thinking, communication, and collaboration skills. Assessment was carried out holistically through diagnostic tests, formative assessments, attitude observations, and learning reflections. Innovations included the use of digital media, storytelling, and the integration of religious activities beyond the classroom. The main challenges comprised limited facilities, the readiness of senior teachers to adapt to technology, and students’ mindsets still accustomed to traditional learning patterns. In conclusion, the implementation of KMA No. 347 at MAN 2 Langkat Tanjung Pura successfully encouraged PAI learning that is more independent, innovative, and oriented toward character development. Keywords: Teacher strategies, Islamic Religious Education, KMA No. 347 of 2022, Merdeka Curriculum, MAN 2 Langkat